Inovasi Ecoprint Mug Berbahan Alami sebagai Sarana Pemberdayaan Perempuan di Desa Suci : Inovasi Ecoprint Mug Berbahan Alami sebagai Sarana Pemberdayaan Perempuan di Desa Suci - Wahyuni, Sri; Widiyanti , Bela Putri; Zama , Berliana Nandya; Pratiwi , Dika Ning; Pratiwi , Reza Yunita; Astuti, Soekma Yeni; Siswono, Hendrik (Dedication : Jurnal Pengabdian Masyarakat, 2025)
Ecoprint batik innovates traditional batik art by using leaves, flowers, and plants to create environmentally friendly motifs. While ecoprint has typically been applied to fabric, bags, or paper, evolving creativity and lifestyle needs call for new media to enhance variety and market value. Mugs present a promising option. The Community Empowerment Partnership (PKM) program in Suci Village, Panti District, Jember Regency, aims to empower women by offering ecoprinting training on mugs using natural materials. This activity has three stages: preparation, implementation, and evaluation. As a result, participants have improved their skills, creativity, and environmental awareness. The ecoprint batik training resulted in the creation of unique mugs featuring natural motifs from leaves and flowers, printed directly on their surfaces. The motifs vary depending on the type of leaf; for instance, teak leaves produce coarse fiber designs.